Drugs and supplements in amateur boxing: pugilistic amateurism and ideologies of performance - Matthews, C. R.; Jordan, M. (Qualitative Research in Sport, Exercise and Health, 2020)
This research, which is based on the thoughts and experiences of coaches, athletes, officials and others involved in amateur boxing, explores the use of recreational drugs, supplements and performance-enhancing drugs in the sport. After providing some context through a discussion of ideologies that shape elite sport, some key methodological issues are briefly described. The findings explore the manner in which ideologies of performance are shaped in relation to the notion of `pugilistic amateurism`. In this way, the paper maps out a theoretical scaffold that can be used to understand the manner in which `old school` training methods and participation in sport align with `traditional` understandings of work-class manhood to produce an ideological tension with a win-at-all-costs mentality. This sheds light on the ways that boxing gyms might be understood as havens where drugs use can be resisted at the same times as potentially positive behaviours can be learned.